2016
DOI: 10.1002/jaba.357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the good behavior game across classroom contexts

Abstract: The Good Behavior Game (GBG), a well-researched classroom group contingency, is typically played for brief periods of time, which raises questions about the effects on subsequent contexts. This study used a multiple baseline design and showed that when the GBG was implemented in one context, behavior improved in only that context. Behavior improved in the subsequent activity only when the GBG was implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 8 publications
2
28
0
3
Order By: Relevance
“…In most versions of the game, violating rules results in receiving points against the team (e.g., Barrish et al, 1969;Donaldson, Vollmer, Krous, Downs, & Berard, 2011;Harris & Sherman, 1973;Mitchell, Tingstrom, Dufrene, Ford, & Sterling, 2015). Other versions have taken a less punitive approach, whereby rule following results in accruing points (e.g., Fishbein & Wasik, 1981;Groves & Austin, 2017;Pennington & McComas, 2017). The GBG typically employs an interdependent group contingency (Litow & Pumroy, 1975), whereby points are earned as a team rather than as individuals.…”
mentioning
confidence: 99%
“…In most versions of the game, violating rules results in receiving points against the team (e.g., Barrish et al, 1969;Donaldson, Vollmer, Krous, Downs, & Berard, 2011;Harris & Sherman, 1973;Mitchell, Tingstrom, Dufrene, Ford, & Sterling, 2015). Other versions have taken a less punitive approach, whereby rule following results in accruing points (e.g., Fishbein & Wasik, 1981;Groves & Austin, 2017;Pennington & McComas, 2017). The GBG typically employs an interdependent group contingency (Litow & Pumroy, 1975), whereby points are earned as a team rather than as individuals.…”
mentioning
confidence: 99%
“…Originally described by Barrish, Saunders, and Wolf (1969), the GBG is a class-wide interdependent group contingency in which (a) classroom rules are developed, (b) students are assigned to teams and monitored for rule violations, (c) teams are given demerits if any student on the team violates a rule, and (d) rewards are provided to all students on the team if the team scores below a predetermined demerit limit. The GBG has been successfully implemented across a range of student ages from kindergarten (Donaldson, Vollmer, Krous, Downs, & Berard, 2011) to high school (Flower, McKenna, Bunuan, Muething, & Vega, 2014;Kleinman & Saigh, 2011;Salend, Reynolds, & Coyle, 1989;Tingstrom et al, 2006), and in a variety of school settings, including general education classrooms (Barrish et al, 1969;Pennington & McComas, 2017), special education classrooms (Breeman et al, 2015;Gresham & Gresham, 1982;Groves & Austin, 2017;Joslyn, Vollmer, & Hernández, 2014), libraries (Fishbein & Wasik, 1981), cafeterias (McCurdy, Lannie, & Barnabas, 2009), and recreational facilities (Galbraith & Normand, 2017). In addition, longitudinal studies have indicated that the GBG could have long-term effects on students, such as reduced rates of substance-use disorders, smoking, antisocial behavior, incarceration, suicidal ideation, and use of mental health services at the ages of 19-21 (Kellam et al, 2011).…”
mentioning
confidence: 99%
“…Another limitation of the GBG literature is that previous research has primarily included data collection and analysis of group data (e.g., mean levels of behavior of a group of children or entire class of children). Although a few studies have included data collection and analysis of individual participant data (McGoey, Schneider, Rezzetano, Prodan, & Tankersley, 2010;Medland & Stachnik, 1972;Pennington & McComas, 2017;Swiezy et al, 1992;Tanol, Johnson, McComas, & Cote, 2010), most either do not report those data or only report the data for the most disruptive children. One exception is a recent study by Groves and Austin (2017) in which the experimenters compared two versions of the GBG in a classroom for students with severe emotional and behavioral disorders.…”
mentioning
confidence: 99%